2011
DOI: 10.4318/tjg.2011.0175
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s wort (Hypericum perforatum) and warfarin: Dangerous liaisons!

Abstract: An 85-year-old male patient with a history of hypertension, old anterior wall myocardial infarction and atrial fibrillation was placed on warfarin one year previously. However, he did not comply with regular international normalized ratio (INR) measurements, but kept taking warfarin (5 mg) on a daily basis for almost a year without any problems. After watching a television program about herbal remedies, he decided to take St John's wort on his own initiative. One month later, he reported to the emergency servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…In particular, hypericin and hyperforin are reported to be respectively CYP1A2 and CYP3A4 inducers [ 7 ]. Thus, attention should be paid when Hypericum is administered in combination with other medications in general [ 12 , 13 ] and more specifically with drugs such as antiretrovirals [ 14 ], cyclosporine [ 15 ], anticoagulants [ 16 ], hormonal contraceptives [ 17 ], and other psychotropic agents such as antidepressants [ 15 ] and antipsychotics [ 18 ]. The number of neurotransmitter systems potentially involved in the mechanism of action of Hypericum is remarkable, encompassing not only monoamines (serotonin, noradrenaline, and dopamine), for which the antidepressant effect is hypothesized, but also glutamate and ion channels [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hypericin and hyperforin are reported to be respectively CYP1A2 and CYP3A4 inducers [ 7 ]. Thus, attention should be paid when Hypericum is administered in combination with other medications in general [ 12 , 13 ] and more specifically with drugs such as antiretrovirals [ 14 ], cyclosporine [ 15 ], anticoagulants [ 16 ], hormonal contraceptives [ 17 ], and other psychotropic agents such as antidepressants [ 15 ] and antipsychotics [ 18 ]. The number of neurotransmitter systems potentially involved in the mechanism of action of Hypericum is remarkable, encompassing not only monoamines (serotonin, noradrenaline, and dopamine), for which the antidepressant effect is hypothesized, but also glutamate and ion channels [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, crossover study in 12 healthy subjects, one tablet of St John's wort (each tablet containing standardized dry extract equivalent to 1 g Hypericum perforatum flowering herb top, 0.825 mg hypericin and 12.5 mg hyperforin) three times daily for two weeks modestly decreased the AUC of both R - and S -warfarin by about 25% after a single 25 mg dose of warfarin [ 91 ]. However, in another case, an 85-year-old patient taking warfarin 5 mg daily was reported to develop upper gastrointestinal bleeding one month after starting St John's wort (without dosage information) [ 122 ]. Until now, the potential interactions between warfarin and St John's wort have not been systemically investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In an open‐label study of healthy subjects, warfarin was demonstrated to induce the clearance of both S‐ and R‐warfarin, with resultant reduction in the effects on INR . In contrast, one case report of supratherapeutic INRs in a patient taking St. John's wort and warfarin concurrently documented the patient's development of a severe bleeding diathesis, manifested by hematemesis and melena . As this is the only such documented interaction predisposing to a bleeding diathesis, one wonders if St. John's wort was responsible for this.…”
Section: Specific Drug‐drug Interactions By Psychotropic Classmentioning
confidence: 98%